Edukasi Pencegahan Hipertensi Menuju Lansia Sehat Di Dusun Tegaltandan, Desa Banguntapan, Bantul - Liena Sofiana (Universitas Lancang Kuning, 2020)
Hypertension is still one of the health problems in Indonesia with a high blood pressure population prevalence of 34.11%. Based on data from the Yogyakarta City Health Office in 2018 hypertension cases were found as many as 18,945 cases. In the Health Profile of Banguntapan III Health Center in 2016, hypertension was number 1 of the top 10 diseases based on visits to the Banguntapan III Health Center. The increase in this case can be caused by several factors, namely the lack of knowledge, attitudes that people have about hypertension so that people have a low behavior to make efforts to prevent hypertension. Health education about hypertension with counseling methods and poster media is one way to increase knowledge. The purpose of this activity is to find out the description of knowledge about hypertension through counseling at the Elderly Posyandu of Tegaltandan. The method used is interactive counseling for the elderly in Tegaltandan directly with poster media. The results obtained were health counseling activities at the Posyandu Elderly running well and smoothly, participants actively gave questions and followed the activities from start to finish conducive.